Cervical Metastasis of Unknown Primary: Use of Discovering Occult Primary Lesions. (23rd August 2013) - Davis, Kara; Byrd, James K.; Mehta, Vikas; Kim, Seungwon; Ferris, Robert L.; Johnson, Jonas T.; Duvvuri, Umamaheswar
Abstract : Objectives: Cancer of an unknown primary squamous cell carcinoma (CUP) metastatic to cervical lymph nodes is a challenging problem for the treating physician. The use of discovering the primary lesion in these patients with regards to oncologic outcomes remains unclear. Our aim is to determine if identification of the primary is associated with improved oncologic outcomes. Methods: Records of 136 patients initially diagnosed as CUP were retrospectively reviewed (1980‐2010). Patients were divided into 2 cohorts based on discovery of the primary lesion. Primary outcome measures were overall survival and time to recurrence according to Kaplan‐Meier analysis. A nested subset of 34 patients in which the primary was discovered were matched to 34 patients remaining undiscovered according to nodal stage and age. Matched‐pair analysis was compared using the stratified Cox regression model. Results: Discovery of the occult primary was associated with improvement in overall survival (10.19 vs 8.83 years, P < 0.001) when stratified across N1‐N2c disease. Matched‐pairs analyses demonstrated that discovery of the primary was associated with better overall survival (hazard ratio [HR] = 0.222; 95% confidence interval [CI] 0.06 to 0.81; P = 0.023). Discovery of the primary trended towards association with lower recurrence (HR = 0.33; 95% CI 0.09 to 1.19; P = 0.091). Conclusions: Discovery of the primary lesion is associated with improved overall survival in patients initially presenting as CUP, both in matched‐pair and cohort comparison analyses. Within this subset, improved locoregional control with discovery of the primary was suggested by a trend towards decreased recurrence. Further studies may clarify treatment discrepancies and molecular differences.